A Discontinuous Finite Volume Method for the Darcy-Stokes Equations. (27th December 2012) - Yin, Zhe; Jiang, Ziwen; Xu, Qiang
Abstract : This paper proposes a discontinuous finite volume method for the Darcy-Stokes equations. An optimal error estimate for the approximation of velocity is obtained in a mesh-dependent norm. First-orderL 2 -error estimates are derived for the approximations of both velocity and pressure. Some numerical examples verifying the theoretical predictions are presented.